Sejarah Kepemimpinan Wanita di Timur Tengah Dalam Tinjauan Hukum Islam (Analisa Terhadap Syajar al Durr) - Meirison Meirison (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Syajar al Durr is a controversial figure who has been instrumental in saving Egypt and the two holy cities of makkah and madina from the western military in the seventh crusade. The victors of the Crusades and the emergence of Mamalik have changed legal decisions against the leadership of women who were previously taboo in the Middle East. Siyasah Syar'iyah is adapted to benefit purposes, although Syajar al Durr has many shortcomings but the legal status has changed with him due to his ability and intelligence. By using historical approaching, the researcher conducted a literature study on politics and Islamic law in women's leadership.In a descriptive way, this study explains about the differences in legal viewpoints, between classical scholars such as at-Tabari, Izzudin bin Abdissalam with the opinions of contemporary scholars such as al-Qardhawi and Ali Jumu'ah which allow women to become heads of state and not priests (caliphs). This research shows that there were some contradictions between the traditional laws and social contemporary perspectives.